The Global Environment of Vaccination Mandates - Dean Abramson, Brian; Vantrees, Ashira (Medicine, Law & Society, 2022)
The COVID-19 pandemic demonstrated how our global economy permits the quick spread of diseases and requires States to engage in a global response to effectively manage this spread. At the core of this response, is the individual State’s responses towards limiting the spread of viruses through vaccinations. However, due to diverse political, cultural, societal, and legal structures, States still do not have a uniform approach to responding to COVID-19. Thus, this article addresses the history of vaccines and the globalization of vaccine law during the COVID-19 pandemic, including the role of vaccination mandates. Moreover, this article discusses how State mandates to vaccination can be developed through legal and political means but also through cultural and societal structures. This article also addresses the impact of disinformation and misinformation in a State’s successful implementation and dissemination of vaccines. Lastly, this article briefly discusses the vaccine injury compensation system in select States and under the COVAX vaccination program.